Comparing slow and rapid bolus of ephedrine in pregnant patients undergoing planned cesarean section under spinal anesthesia - Prabu Gunasekaran; Lenin Babu Elakkumanan; Hemavathi Balach; M. V. S. Satyaprakash (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: While ephedrine was the preferred drug for treating spinal-induced hypotension in pregnancy, its use has declined because of resultant fetal acidosis. The objective of this randomized control trial was to compare the effects of a slow and rapid bolus of ephedrine on fetal acidosis, maternal blood pressure, and heart rate (HR) during cesarean section performed under spinal anesthesia. Material and Methods: Eighty full-term parturients scheduled for cesarean section under spinal anesthesia were randomly allocated into two groups. While both groups received 6 mg of ephedrine to treat hypotension, Group R (n = 40) received it as a rapid intravenous bolus and Group S (n = 40) received it slowly over 20 s with an infusion pump. The maternal vital parameters were recorded until delivery of the baby using a video camera. Umbilical cord blood was obtained using the three clamp method. Hemodynamic parameters, fetal acidosis, total number of ephedrine bolus used, peak HR after the ephedrine bolus, and occurrence of postoperative nausea and vomiting (PONV) were compared between the groups. Results: Mean increase in HR and blood pressure were significantly higher in Group R than the Group S after the first ephedrine bolus. Umbilical artery pH was significantly lower in Group R than in Group S (7.2 [6.8-7.3] vs. 7.3 [7.3-7.4], P < 0.01). A total number of ephedrine boluses were comparable in the two groups. 35% of the patients had PONV in Group R, whereas none had it in Group S (P < 0.01). Conclusion: Slow bolus of ephedrine is better than rapid bolus to treat spinal-induced hypotension during cesarean section in view of less fetal acidosis.